THE IMPLEMENTATION PRACTICES OF PERFORMANCE-BASED BUDGETING SYSTEMS IN FOREIGN COUNTRIES - Bakhtiyor Artikov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article presents the implementation and evolutionary development of the performance-based budgeting system in foreign countries, as well as the goals and objectives of introducing performance-based budgeting in Uzbekistan.